2014
DOI: 10.1155/2014/349325
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation inToxoplasma gondii rop17Gene among Strains from Different Hosts and Geographical Locations

Abstract: Genetic diversity of T. gondii is a concern of many studies, due to the biological and epidemiological diversity of this parasite. The present study examined sequence variation in rhoptry protein 17 (ROP17) gene among T. gondii isolates from different hosts and geographical regions. The rop17 gene was amplified and sequenced from 10 T. gondii strains, and phylogenetic relationship among these T. gondii strains was reconstructed using maximum parsimony (MP), neighbor-joining (NJ), and maximum likelihood (ML) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Of these variable positions, 18 were transitions (A↔G and C↔T) and 11 were transversions (A↔C, A↔T, G↔C, and G↔T) in the coding region of the ROP20 gene (R = transition/transversion = 1.6). These results were similar to those found in previous studies for Hsp60 and ROP17 (Lu et al, 2014;Zhang et al, 2014).…”
Section: Resultssupporting
confidence: 93%
“…Of these variable positions, 18 were transitions (A↔G and C↔T) and 11 were transversions (A↔C, A↔T, G↔C, and G↔T) in the coding region of the ROP20 gene (R = transition/transversion = 1.6). These results were similar to those found in previous studies for Hsp60 and ROP17 (Lu et al, 2014;Zhang et al, 2014).…”
Section: Resultssupporting
confidence: 93%
“…Based on the partial sequences of the SOD locus, phylogenetic analysis revealed 2 major clusters with only a little difference of bootstrap values, and it cannot differentiate T. gondii strains to their genotypes, implying a low genetic diversity. Our results were similar to some studies such as MIC13, eIF4A [ 25 , 26 ] and different from other genetic markers including GRA5, GRA6, and ROP17 [ 21 - 23 ]. The low sequence variation (0-1.0%) in the partial SOD gene suggests that SOD gene could not be an ideal genetic marker for differentiation of the T. gondii strains or intraspecific phylogenetic analyses.…”
Section: Discussionsupporting
confidence: 89%
“…GRA5, GRA6, and ROP17) have shown signs of positive selection, and could be sufficient for genotyping of T. gondii isolates. [ 21 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The restriction fragments were resolved in 3% agarose gel, stained by the GoldenView™, and photographed by a gel documentation system (UVP GelDoc-It TM Imaging System, Cambridge, UK). (Chen et al, 2012;Zhang et al, 2014;Fazaeli et al, 2000). Our results indicated that ROP47 gene sequences are conserved within a genotype, but are highly divergent among different T. gondii genotypes.…”
Section: Genetic Characterization Of T Gondii Dna Isolates By Pcr-rflpmentioning
confidence: 52%
“…Phylogenetic reconstruction was based on the ROP47 gene sequences determined in the present study plus the corresponding sequences of strains VEG and ME49 available in ToxoDB (http://toxodb.org/toxo/) using three methodologies, namely maximum parsimony (MP), maximum likelihood (ML) and neighbor-joining (NJ), with the sequence of Neospora caninum (NCLIV_025740) as the outgroup. These methodologies analysis were performed using PAUP* 4.0b10 (Swofford, 2002), following previous studies Chen et al, 2012a;Zhang et al, 2014). Phylograms were drawn by the Tree View program version1.65.…”
Section: Sequence Analysis and Phylogenetic Reconstructionmentioning
confidence: 99%